2020
DOI: 10.1063/5.0002602
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional microscopy by ultrasonic sample control

Abstract: Omnidirectional microscopy (OM) is an emerging technology capable of enhancing the threedimensional (3D) microscopy widely applied in life sciences. In OM, precise position and orientation control of the sample are required. However, current OM technology relies on destructive, mechanical methods to hold the samples, such as embedding samples in gel or attaching them to a needle to permit orientation control. A non-contacting alternative is to levitate the sample. Up until now levitation methods have lacked or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We recently developed an acoustic levitation method capable of full 3-axis orientation control of asymmetric samples [6]. This was achieved with a spatially asymmetric vortex trap created with PAT, whose phases and amplitudes were set according to our method.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed an acoustic levitation method capable of full 3-axis orientation control of asymmetric samples [6]. This was achieved with a spatially asymmetric vortex trap created with PAT, whose phases and amplitudes were set according to our method.…”
Section: Introductionmentioning
confidence: 99%
“…The control of acoustic levitation process in all of its stages had seen some traditional control strategies which applied to achieve the desired performance, but it has not yet been proven that an object can be rotated in three dimensions under control. A comprehensive control over the orientation in three dimensions for a non-spherical object only by accurately aligned the acoustic trap using a devised algorithm, and a phased-array transducer (PAT)-based levitator was created specifically for this study demonstrated by [171] which would allow implementations in spectroscopy, photogrammetry, and contactless placement. Up to now, the orientation has only been controlled in one dimension according to [140], [161].…”
Section: Control Strategies For Acoustic Levitationmentioning
confidence: 99%
“…The 3D orientation control can be used to handle fragile samples and therefore has applications in industry and medicine. The applications vary from contactless 3D imaging [4] to moving electronic components [5].…”
Section: Introductionmentioning
confidence: 99%